Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ajmg.b.32612
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioral problems in children and adolescents with neurofibromatosis type 1

Abstract: To assess emotional and behavioral problems in children and adolescents with neurofibromatosis type 1,parents of 183 individuals aged 10.8 ± 3.1 years (range 6-17) completed the Child Behavior Checklist (CBCL). Also, 173 teachers completed the Teacher's Report Form (TRF), and 88 adolescents (children from 11 to 17 years) completed the Youth Self-Report (YSR). According to parental ratings, 32% scored in the clinical range (above the 90th percentile). This percentage was much lower when rated by teachers or ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 27 publications
(36 reference statements)
7
19
1
4
Order By: Relevance
“…Parents in the study rated their children as having significantly greater symptomatology than children reported in their self‐ratings. This finding is consistent with other studies of children with NF1 (Krab et al, ; Rietman et al, ), as well as research that has looked more broadly at children with chronic illness and also healthy children with a sibling with chronic illness (Sharpe & Rossiter, ).…”
Section: Discussionsupporting
confidence: 91%
“…Parents in the study rated their children as having significantly greater symptomatology than children reported in their self‐ratings. This finding is consistent with other studies of children with NF1 (Krab et al, ; Rietman et al, ), as well as research that has looked more broadly at children with chronic illness and also healthy children with a sibling with chronic illness (Sharpe & Rossiter, ).…”
Section: Discussionsupporting
confidence: 91%
“…With regard to emotional and behavioral problems, some studies have evaluated children and adolescents with NF1 through the parents' compilation of Child Behavior Checklist (CBCL) questionnaires. Rietman et al [21] showed that of 183 subjects 32% fell in the clinical range, considering Total scores. Graf et al [22] identified problems predominantly in the internalizing domain of anxiety, depression, social withdrawal and somatic complaints.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cognitive deficits include a generalized downshifting Intelligence Quotient (IQ) with cognitive delay in about 4–8% of the patients [ 4 ], impairment in visuo-spatial skills in the majority of NF1 children [ 13 , 14 ], in specific academic domains of reading, spelling, and mathematics in up to 75% [ 15 , 16 ], and attention problems including ADHD in 60% [ 17 19 ]. Difficulties in social functioning with increased rates of ASD are seen in 11% of the patients [ 20 ], and mood/anxiety disorders [ 21 ] encompassing anxiety, depression, social withdrawal, and somatic complaints have been reported [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The eff ect of dopamine in these disorders has also been explored. Further there are att empts to include social networks in aiding patients and their parents to bett er understand the diffi culties and reduce their isolation (26)(27)(28). Results of the study concerning emotional and behavioural problems in children and adolescents with NF 1 (26) showed that att entional problems were associated with lower verbal IQ, male gender, younger age and ADHD-symptoms.…”
Section: Cognitive Diffi Culties and Neurofi Bromatosis Typementioning
confidence: 99%
“…Further there are att empts to include social networks in aiding patients and their parents to bett er understand the diffi culties and reduce their isolation (26)(27)(28). Results of the study concerning emotional and behavioural problems in children and adolescents with NF 1 (26) showed that att entional problems were associated with lower verbal IQ, male gender, younger age and ADHD-symptoms. A systematic review of literature regarding behaviour of children and adolescents with NF1 show signifi cant alterations in language, reading, visuospatial skills, motor function, executive function, att ention, behaviour, emotion and social skills.…”
Section: Cognitive Diffi Culties and Neurofi Bromatosis Typementioning
confidence: 99%